Changes in heavy metal accumulation in some edible landscape plants depending on traffic density - Sevik, Hakan; Cetin, Mehmet; Ozel, Halil Baris; Ozel, Senem; Zeren Cetin, Ilknur (Environmental monitoring and assessment, 2020)
Food scarcity is one of global issues that our world faces today. A significant portion of the world’s population has no access to adequate food, and it is stated that approximately 830 million people suffer from chronic famine. This predicament is estimated to grow even further. Many attempts have been made to solve the food problem. Some examples are using new resources which have not been used for dietary purposes up to this point, planting new areas to produce food products, and increasing the potential harvest per an area unit. One of the solution proposals, which has come up recently within this scope, is the term of “edible landscaping”, which means the use of edible plants in the landscaping works, and thus maximizing the potential for food security. However, edible landscaping poses a considerable risk. Heavy metal accumulation in plants grown in urban centers can reach to high levels, and consuming these plants will allow these heavy metals a direct access into the human body and wreak havoc to the public health. But since this subject has not been sufficiently studied yet, the extent of such a risk is not accurately determined yet. This study aims to determine the changes of Ni, Co and Mn concentrations depending on traffic density in the leaves, branches, barks and fruits of cherry, plum, mulberry and apple trees growing in areas with dense traffic, low-density traffic and no-traffic zones in Kastamonu province. The results showed that the concentrations of Ni and Co elements increased in many organelles depending on traffic density, and that the heavy metal concentrations in fruits could be very high. This situation indicates that fruit and vegetables grown in industrial zones and urban centers, where heavy metal pollution may be high, can be harmful to the public health if consumed as crops.